Play in a Covid Frame Everyday Pandemic Creativity in a Time of Isolation - Beresin, Anna; Bishop, Julia (Open Book Publishers, 2023)
During the international coronavirus lockdowns of 2020-2021, millions of children, youth, and adults found their usual play areas out of bounds and their friends out of reach. How did the pandemic restrict everyday play and how did the pandemic offer new spaces and new content? This unique collection of essays documents the ways in which communities around the world harnessed play within the limiting frame of Covid-19. Folklorists Anna Beresin and Julia Bishop adopt a multidisciplinary approach to this phenomenon, bringing together the insights of a geographically and demographically diverse range of scholars, practitioners, and community activists. The book begins with a focus on social and physical landscapes before moving onto more intimate portraits of play among the old and young, including coronavirus-themed games and novel toy inventions. Finally, the co-authors explore the creative shifts observed in frames of play, ranging from Zoom screens to street walls. This singular chronicle of coronavirus play will be of interest to researchers and students of developmental psychology, childhood studies, education, playwork, sociology, anthropology and folklore, as well as to toy, museum, and landscape designers. This book will also be of help to parents, professional organizations, educators, and urban planners, with a postscript of concrete suggestions advocating for the essential role of play in a post-pandemic world.